Managing change in academic libraries - Yermekpayeva, Tendik (My University, 2014)
This course helps to those who take this course adjust to changes in the library. Mostly changes are directed on improving services rendered to patrons. As far as libraries are constantly improving services, librarians should manage changes to increase success and to minimize the stress that they experience.
Association of college and research libraries e-learning course conducted by American Library Association online continuing education
Keywords: managing change; developmental change; transitional change; transformational change; principles for managing change